Gaps And Needs of Education Facilities in Majene Regency - mukhlis, Jafar; Lestari, Sri Apriani Puji; Asriana, Zul; Munaja, Rahmiyatal; Hariani, Mira Lestira (Journal of Green Science and Technology, 2024)
Majene Regency is located in West Sulawesi Province and is designated as a provincial education area causing the population to increase, the increase in population is not accompanied by an increase in the number of educational facilities which causes a lack of access to education. This study aims to determine and analyze the gap in educational facilities in Majene Regency and analyze the needs of ideal educational facilities in Majene Regency. This research is descriptive quantitative research, namely research that describes variables as they are supported by data in the form of numbers generated from actual circumstances. The result of this research is that most districts have educational facilities such as kindergarten, elementary school, junior high school, and high school. Only Banggae district and Tubu Sendana district and Ulumanda district do not have high school facilities. The education distribution gap occurs in Majene Regency, Majene Urban Area is most dominant in lacking educational facilities compared to other districts. This is not correlated with the status of the urban center which in fact provides and has more facilities and services than other districts. Efforts are needed to improve and develop educational facilities by adding educational facilities, especially high school education facilities, which have the highest demand. Keyword: facilities, distribution, needs, education.